(untitled) (Libellarium: journal for research in the field of information and related sciences, 2012)
The aim of the paper is the research of transformation of formatting information on banknotes during the 20th century, which is the period of some of the greatest graphical innovations after Gutenberg’s invention of movable type printing. Computer graphics had taken over in the field of typography in the exact moment of hand engraving’s highest level of art in the creation of the font cut. About forty years ago, the era of etching used in copper etching and steel engraving in hand - made drawings had begun, along with the use of phototypesetting as the representative of digital technology. Quality of the written lines has introduced microtypography as a special method of rasterization in the background of banknotes. In Croatia, the above mentioned modifications are present through the works of our typographers, even though the multiplication of banknotes was done in foreign printing houses that had appropriately protected printing technology. The paper contributes to the scientific analysis of the technical aspect of banknote making on Croatia’s soil during the course of the 20th century, and this, with the methods of analysis and synthesis incorporated, gives a clear picture and transparency into the method of banknote making, both from a technological and development cycle - making aspect. Given the fact that not only the Croatian banknotes are examined, analysis contributes to comparative procedures of local scopes in the field of technological manufacture of other banknotes that belong to the same time period.